All‐Small‐Molecule Organic Solar Cells with Efficiency Approaching 16% and FF over 80%. Issue 21 (21st April 2022) - Meng, Lingxian; Li, Mingpeng; Lu, Guanyu; Shen, Zichao; Wu, Simin; Liang, Huazhe; Li, Zhixiang; Lu, Guanghao; Yao, Zhaoyang; Li, Chenxi; Wan, Xiangjian; Chen, Yongsheng
Abstract: Molecule engineering has been demonstrated as a valid strategy to adjust the active layer morphology in all‐small‐molecule organic solar cells (ASM‐OSCs). In this work, two non‐fullerene acceptors (NFAs), FO‐2Cl and FO‐EH‐2Cl, with different alkyl side chains are reported and applied in ASC‐OSCs. Compared with FO‐2Cl, FO‐EH‐2Cl is designed by replacing the octyl alkyl chains with branched iso ‐octyl alkyl chains, leading to an enhanced molecular packing, crystallinity, and redshifted absorption. With a small molecule BSFTR as donor, the device of BSFTR:FO‐EH‐2Cl obtains a better morphology and achieves a higher power conversion efficiency (PCE) of 15.78% with a notable fill factor ( FF ) of 80.44% than that of the FO‐2Cl‐based device with a PCE of 15.27% and FF of 78.41%. To the authors' knowledge, the FF of 80.44% is the highest value in ASM‐OSCs. These results demonstrate a good example of fine‐tuning the molecular structure to achieve suitable active layer morphology with promising performance for ASM‐OSCs, which can provide valuable insight into material design for high‐efficiency ASM‐OSCs. Abstract : A non‐fullerene acceptor, FO‐EH‐2Cl with branched alkyl side chains on the molecular backbone is designed to subtly manipulate the active layer morphology for all‐small‐molecule organic solar cells. A BSFTR:FO‐EH‐2Cl‐based device achieves a power conversion efficiency (PCE) of 15.78% with an outstanding fill factor ( FF ) of 80.44%.